Cerebral Gluconeogenesis and Diseases - Yip, James; Geng, Xiaokun; Shen, Jiamei; Ding, Yuchuan (Frontiers in Pharmacology, 2017)
The gluconeogenesis pathway, which has been known to normally present in the liver, kidney, intestine, or muscle, has four irreversible steps catalyzed by the enzymes: pyruvate carboxylase, phosphoenolpyruvate carboxykinase, fructose 1,6-bisphosphatase, and glucose 6-phosphatase. Studies have also demonstrated evidence that gluconeogenesis exists in brain astrocytes but no convincing data have yet been found in neurons. Astrocytes exhibit significant 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase-3 activity, a key mechanism for regulating glycolysis and gluconeogenesis. Astrocytes are unique in that they use glycolysis to produce lactate, which is then shuttled into neurons and used as gluconeogenic precursors for reduction. This gluconeogenesis pathway found in astrocytes is becoming more recognized as an important alternative glucose source for neurons, specifically in ischemic stroke and brain tumor. Further studies are needed to discover how the gluconeogenesis pathway is controlled in the brain, which may lead to the development of therapeutic targets to control energy levels and cellular survival in ischemic stroke patients, or inhibit gluconeogenesis in brain tumors to promote malignant cell death and tumor regression. While there are extensive studies on the mechanisms of cerebral glycolysis in ischemic stroke and brain tumors, studies on cerebral gluconeogenesis are limited. Here, we review studies done to date regarding gluconeogenesis to evaluate whether this metabolic pathway is beneficial or detrimental to the brain under these pathological conditions.